Efektivitas Model Problem Based Learning dan Discovery Learning terhadap Berfikir Kritis pada Pembelajaran Matematika: Kajian Meta-Analisis - Maulida Anggraina Saputri; Theresia Sri Rahayu (FONDATIA, 2021)
This study aims to determine the effect of level differences in Problem Based Learning and Discovery Learning model on student’s critical thinking by meta-analysis studies in Mathematics learning, by collecting several relevant journals through Google Scholar. This study uses the Ancove Test to determine the average difference Test in learning model, which has met the Prerequisite Test, then the Effect size is calculated. The result is normal, homogeneous and linear data were obtained with a significance value>0,05. In Ancova Test, the result Discovery Learning is more effective than Problem Based Learning. This is obtained from the results of the posttest scores of 78.4450 for the Problem Based Learning and 83.5840 for the Discovery Learning models. At the Fcount obtained is 7,181, and the Ftable obtained is 3,59, it can be stated that Fcount > Ftable, namely with a value of 7,181 > 3,59 and significance of 0,016 < 0,05. From these results prove that there is a significant difference between the Problem Based Learning and Discovery Learning models on student’s critical thinking in Mathematics learning. In determining the Effect size, it produces a value of 0,0302, it can be stated a moderate influence on student’s critical thinking in Mathematics learning.